Pelatihan PELATIHAN PENINGKATAN KAPASITAS MSAYARAKAT UNTUK PENGELOLAAN KEUANGAN BKM DI KABUPATEN TUBAN: PELATIHAN PENGELOLAAN KEUANGAN BKM DENGAN METODE EXPERIENCE LEARNING CYCLE - Suyitno Suyitno; Yulie Wahyuningsih (CV. Multi Kreasi Media, 2022)
Paying attention to the effectiveness of the role of the Badan Kesawadayaan Masyarakat (BKM) as an entity that was initiated, formed and managed independently by the community through the PNPM-MP program, which later turned into the Kota Tanpa Kumuh (KOTAKU) program. BKM is a forum to accommodate the aspirations and needs of the community in meeting the needs of life from the economic, social and infrastructure aspects of the settlement environment. In building public trust, BKM needs to realize the principles of transparency and accountability in managing the finances spent in realizing its work program. As a form of concrete participation in encouraging the acceleration of the achievement of community welfare through the KOTAKU Program, it is deemed necessary to carry out Community Service which aims to increase the capacity and knowledge of the Secretariat BKM in 17 Kelurahan in the Tuban District, Tuban Regency. The activity begins with a session on delivering theory, practice in preparing financial reports and case studies. Participants were very enthusiastic about participating in the activity from beginning to end and the activity ran smoothly and orderly